The Implementation of Mandatory Salat Through Habituation Method in SMP AL Iman Parakan - Helma Sofnia Adiani (Journal of Islamic Education and Ethics, 2023)
This study aims (1) to find out the implementation of the mandatory prayers at SMP Al Iman Parakan with the habituation method, (2) to find out the supporting and inhibiting factors in the implementation of the mandatory prayers through the habituation method at SMP Al Iman Parakan. The research method used was qualitative research, with descriptive qualitative research types applying the data collection techniques of observation, interviews, and documentation. The data were analyzed based on the reasoning ability of researchers in connecting facts, data, and existing information. The subjects of the research were the principal, the teachers of Islamic Education Subject, and the students. As a result, the extent to which the implementation of mandatory prayer services through the habituation method is found. The results showed that SMP Al Iman had implemented the mandatory prayer through the habituation method by fulfilling the four requirements of the habituation method implementation and having fulfilled three of the four steps of the habituation method implementation. The inhibiting factors in the implementation of this habituation method are laziness, inadequate infrastructure, lack of self-awareness, the influence of the social environment, and difficulties in controlling students. Then, the factors supporting the implementation of this method are the vision and mission of the school, which is based on faith and piety. There is an attendance list for prayers, cooperation between teachers, and the lack of cooperation between teachers.